(untitled) (PJDOL, 2023)
In an open distance English Language learning classroom, teaching writing to a group of adult learners with very minimum exposure to academic writing skills can deem a great challenge for many facilitators. Many of these learners come back to school after long periods of absence and to teach them the sophisticated skills of writing can be an arduous task for many facilitators especially to enable them to participate in communicative interactions and receive constructive feedback on online forums which they are not used to doing. To overcome the documented lack of participation in large forums, the course team decided to look for other asynchronous tools to encourage greater collaboration. This paper discusses the use of Wikis and Blogs in different phases of the writing course and the potential implication issues that need to be considered in the implementation process.